2019
DOI: 10.1101/631960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel genetic circuitry governing hypoxic metabolic flexibility, commensalism and virulence in the fungal pathogen Candida albicans

Abstract: Inside the human host, the pathogenic yeast Candida albicans colonizes predominantly oxygen-poor niches such as the gastrointestinal and vaginal tracts, but also oxygen-rich environments such as cutaneous epithelial cells and oral mucosa. This suppleness requires an effective mechanism to reprogram reversibly the primary metabolism in response to oxygen variation. Here, we have uncovered that Snf5, a subunit of SWI/SNF chromatin remodeling complex, is a major transcriptional regulator that links oxygen status … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Metabolomic approaches brought insight into C . albicans virulence mechanisms, antifungal effects, and biofilm growth [ 6 , 13 , 18 , 21 25 , 28 33 , 35 39 ]. Although one study focused on secreted metabolites and biomarkers in C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomic approaches brought insight into C . albicans virulence mechanisms, antifungal effects, and biofilm growth [ 6 , 13 , 18 , 21 25 , 28 33 , 35 39 ]. Although one study focused on secreted metabolites and biomarkers in C .…”
Section: Discussionmentioning
confidence: 99%
“…A combination of transcriptomic and metabolomic approaches defined the importance of C . albicans Snf5, a subunit of the SWI/SNF chromatin remodeling complex, in controlling metabolic flexibility and fungal fitness specifically under hypoxia [ 33 ].…”
Section: What Have We Learned From Metabolomics Of Human Pathogenic Fmentioning
confidence: 99%
“…GSEA was performed using standard parameters [ 9 ]. Gene lists were filtered as mentioned for GO analysis above.…”
Section: Methodsmentioning
confidence: 99%
“…The functions of the CRCs in relation to the pathogenic attributes of C . albicans are primarily known from the studies on the SWI/SNF complex [ 9 12 ]. However, how other CRCs feed into these pathways to regulate C .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a study by Burgain and colleagues demonstrated that Candida albicans (C. albicans) with Snf5 (also called SMARCB1) mutations cannot grow on alternative carbon sources in hypoxia. However, the mutants can grow normally on fermentable carbohydrates like glucose and fructose (26). The authors determined that Snf5 is required for survival in hypoxia via regulation of carbon flexibility, ultimately concluding that the SWI/SNF complex is a master regulator that connects the oxygen-sensing machinery with carbon utilization in C. albicans.…”
Section: The Swi/snf Complex Regulates Carbon Flexibilitymentioning
confidence: 99%